Formulaic focus-on-form episodes in adult EFL communicative interactions. (August 2017) - Gholami, Leila; Karimi, Mohammad Nabi; Atai, Mahmood Reza
Abstract: The present study investigated three categories of formulaic sequences (FSs), namely, collocations, lexical bundles, and idioms in incidental focus on form (FonF). The data consisted of 30 h of audio-recorded communicative classroom interactions between the teacher and the entire class in three adult English as a foreign language classes. The analysis involved transcription and codification of all focus-on-form episodes (FFEs) divided into formulaic (collocation, lexical bundle, and idiom) and nonformulaic FFEs (grammar, pronunciation, and vocabulary) based on their linguistic foci. Moreover, formulaic episodes were further categorized into reactive versus preemptive and teacher-versus student-initiated FFEs. A total of 1102 instances of FFEs were identified, 38% of which were of formulaic nature. The findings demonstrated that nonformulaic FFEs outnumbered formulaic ones. Preemptive formulaic FFEs and student-initiated episodes were used more frequently than the other types, though not to a great degree. Among the FSs, collocation was the most frequently focused category. Extending the scope of research in FonF studies, this study indicates that FSs account for a substantial proportion of FFEs, and teachers and learners do often make departures from ongoing meaningful interactions to attend to not only nonformulaic linguistic features but also formulaic aspects of language.